K+/Cl− cotransporter 2 (KCC2) and Na+/HCO3− cotransporter 1 (NBCe1) interaction modulates profile of KCC2 phosphorylation - Pethe, Abhishek; Hamze, Mira; Giannaki, Marina; Heimrich, Bernd; Medina, Igor; Hartmann, Anna-Maria; Roussa, Eleni (Frontiers in Cellular Neuroscience, 2023)
K+/Cl- cotransporter 2 (KCC2), is a major Cl- extruder in mature neurons and responsible for establishment of low intracellular [Cl-], necessary for fast hyperpolarizing GABAA-receptor mediated synaptic inhibition. Electrogenic sodium/bicarbonate cotransporter 1 (NBCe1) is a pH regulatory protein expressed in neurons and glial cells. An interactome study has identified NBCe1 as possible interaction partner of KCC2. Here, we investigated putative effect of KCC2/NBCe1 interaction in baseline and stimulus-induced phosphorylation pattern and function of KCC2. Therefore, primary mouse hippocampal neuronal cultures from wildtype (WT) and Nbce1-deficient mice, as well as HEK-293 cells stably transfected with KCC2WT were used. The results show that KCC2 and NBCe1 are interaction partners in mouse brain. In HEKKCC2 cells, pharmacological inhibition of NBCs with S0859 prevented staurosporine- and 4-aminopyridine (4AP)-induced KCC2 activation. In mature cultures of hippocampal neurons, however, S0859 completely inhibited postsynaptic GABAAR and, thus, could not be used as tool to investigate the role of NBCs in GABA-dependent neuronal networks. In Nbce1-deficient immature hippocampal neurons, baseline phosphorylation of KCC2 at S940 was downregulated, compared to WT and exposure to staurosporine failed to reduce pKCC2 S940 and T1007. In Nbce1-deficient mature neurons, baseline levels of pKCC2 S940 and T1007 were upregulated, compared to WT whereas after 4AP treatment pKCC2 S940 was downregulated and pKCC2 T1007 was further upregulated. Functional experiments showed that the levels of GABAAR reversal potential, baseline [Cl-]i, Cl- extrusion and baseline pHi were similar between WT and Nbce1-deficient neurons. Altogether, our data provide primary description of the properties of KCC2/NBCe1 protein-protein interaction and implicate modulation of stimulus-mediated phosphorylation of KCC2 by NBCe1/KCC2 interaction, a mechanism with putative pathophysiological relevance.